Transformations to open market operations : developing economies and emerging markets - Axilrod, Stephen H. (IMF WashingtonUS, 1996)
Provides a brief review of the connection between open market operations and other monetary operations. Discusses how the central bank can encourage development of the necessary financial market architecture. Reviews the advantages and limitations of specific approaches to open market operations.